The environmental, socioeconomic, and health impacts of woodfuel value chains in Sub-Saharan Africa: a systematic map - Sola, P.; Cerutti, P.O.; Zhou, W.; Gautier, D.; Iiyama, Miyuki; Schure, J.; Chenevoy, A.; Yila, Jummai Othniel; Dufe, V.; Nasi, Robert; Petrokofsky, G.; Shepherd, G. (Springer, 2017)
In Sub-Saharan Africa (SSA), the production and use of woodfuel remains an important socio-economic activity with more than 70% of the population relying on woodfuel as their primary household energy source. Despite their socio-economic significance, woodfuel value chains are often viewed negatively due to their association with detrimental health and environmental impacts. However, the lack of sound evidence and limited understanding of the role of contextual factors in influencing the various impacts of woodfuel value chains have prevented the formulation of properly guided policy interventions. Thus the objective of this systematic map is to provide a comprehensive review of the environmental, socio-economic, and health impacts of woodfuel value chains across SSA.The search strategy for this review map was defined in a peer-reviewed protocol and refined by iterative testing. Search strings were composed of population, intervention, and location terms and combined using Boolean operators. The bibliographic databases Web of Science, Scopus, and CAB Abstracts were used as the main sources of literature for this review, and a total of 4728 results were initially retrieved. Following title and abstract screening, 659 entered full text screening. Critical appraisal of 219 articles led to the exclusion of studies that did not set meet quality criteria for this map, resulting in a final total of 131 articles for inclusion in data extraction and analysis.From the 131 included articles, 152 individual studies were identified during data extraction. Studies came from 26 of the 49 Sub Saharan African countries, with a particular preponderance of articles published in the last 10 years. Critical appraisal found significant weaknesses in the experimental design of woodfuel value chain studies with the exception of health impact studies, which frequently utilized controls or other relevant comparators. Findings suggest that woodfuel value chains have environmental, socioeconomic and health consequences with the frequent presence of trade-offs. The reporting of contextual factors in the studies challenge the widespread perception of deforestation as being directly caused by bush fires, overgrazing and woodcutting. Instead, agricultural expansion (which often includes forest clearing) and pre-existing biophysical factors were the most frequently cited factors in shaping environmental outcomes.This systematic map suggests that there are environmental, socioeconomic and health consequences associated with woodfuel value chains in Sub-Saharan Africa. However, the literature also shows a weak and geographically limited evidence base to justify the above claims. We argue that policy formulation processes targeting woodfuels in SSA require more solid, coherent and broad body of knowledge, especially for such a vital sector in rural economies. Thus, there is an urgent need to design and undertake research using robust methodologies, at appropriate scales that further takes into account the interrelationships between environmental and socio-economic outcomes in order to generate substantial and reliable evidence for informed policy formulation.